Analysis of the Implementation of Total Productive Maintenance (TPM) at Madam Souvenir - Purba, Angel Theresia; Utami, Mulia; Lubis, Rahma Safitri; Gultom, Pesta (Economic: Journal Economic and Business, 2025)
This research aims to analyze the implementation of Total Productive Maintenance (TPM) at the Madam Souvenir Bakery in order to increase the effectiveness of production machines. The method used is Overall Equipment Effectiveness (OEE) measurement to assess machine performance based on three factors: availability, performance and quality. The OEE calculation results show a value of 72.2%, which is below the ideal standard of 85%. In-depth analysis identified "speed losses" as the main factor influencing the decline in machine effectiveness. To overcome this problem, several recommendations were implemented, including independent maintenance by the operator and a regular maintenance schedule (planned maintenance). The implementation of TPM has proven to be effective in minimizing losses due to downtime and improving product quality. It is hoped that the results of this research can help Madam Souvenir Bakery achieve production targets more efficiently.